Promosi Makanan Tradisional Lokal Untuk Meningkatkan Pariwisata Kuliner Pada Pasar Bojong Pekalongan - Ilma Nafiyah; Misel Yulianti; Ayu Tyas Styaningsih; Muhammad Taufiq Abadi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Indonesia is a developing country with many potential tourist destinations, natural tourism and cultural tourism in each region because Indonesia has different tribes, customs, cultures and geographical location. Indonesia is a tropical country that produces. Indonesia also has many traditional snacks in each region, Indonesian traditional snacks are one of the legacies of our ancestors that must be preserved and preserved so that they are not forgotten by future generations. However, currently Indonesian people prefer snacks such as pizza, hamburgers and other snacks as they develop. In western culture, it is not uncommon for children to be asked if they don't know the traditional food of their area. Therefore, let's preserve traditional snacks by buying traditional snacks, learning how to make them, practicing recipes, and also helping to market and introduce traditional snacks to the general public. Communication is one of the most important aspects in marketing the tourism industry in an area, according to Soemanagara (2008), this service activity provides various benefits, knowledge and skills to Bojong Pekalongan market traders to increase culinary tourism in the Bojong Pekalongan market. Promotion of local traditional food Bojong Pekalongan market traders are trained to promote local traditional food on social media using mobile media such as Traditional food is apem cake, ball baling and others.